Model Pembelajaran Bahasa Indonesia di MI/SD - Rohmah Ivantri (STIT Al-Quraniyah Manna, 2021)
Learning activities in schools, known as the learning model. The learning model is a reference or guide for a teacher in selecting or implementing learning activities to be carried out. In Indonesian language lessonss in primary school/ Madarasah Ibtidaiyah (MI), to meet the achievement of learning objectives, it is necessary to determine the right learning model. Because Indonesian subjects in primary school/ MI are not only taught using Indonesian, but there must be activities that are interesting for students to want to take part in these learning activities. Meanwhile, in determining the learning model, it is necessary to pay attention to its characteristics, types, and applications. This is done so that the delivery of information to students can run smoothly. And various learning models can help teachers overcome learning problems that have been felt to be boring in class. Kata kunci: model pembelajaran, Bahasa Indonesia, MI/SD